Implementasi Kebijakan dan Strategi Pelestarian Kawasan Ekosistem Leuser Provinsi Aceh sebagai Kawasan Strategis Nasional - Nuribadah Nuribadah (Kanun Jurnal Ilmu Hukum, 2012)
ABSTRACT: Article 20 paragraph (6) of the Law No. 26, 2007 on the Spatial Planning states that "National Spatial Plan is regulated by the Government". The Government Regulation Number 26, 2008 stipulates that the Leuser Ecosystem as one of the National Strategic Areas in Aceh province. However, the determination of the Leuser Ecosystem (LE) as a National Strategic Area is not making as the area that has been specifically required, both regional planning and utilization. Many people do not understand the significance of the area as a national strategic and legal implications if the violation of the provisions set out in the Act. Policy and Strategy Implementation on Leuser Ecosystem Area Conservation of Aceh Province as a National Strategic Area